In vivo optical coherence tomography for the diagnosis of oral malignancy - Wilder-Smith, Petra; Jung, Woong-Gyu; Brenner, Matthew; Osann, Kathryn; Beydoun, Hamza; Messadi, Diana; Chen, Zhongping (Lasers in surgery and medicine, 2004)
Background and Objective Oral cancer results in 10,000 U.S. deaths annually. Improved highly sensitive diagnostics allowing early detection of oral cancer would benefit patient survival and quality of life. Objective was to investigate in vivo non‐invasive optical coherence tomography (OCT) techniques for imaging and diagnosing neoplasia‐related epithelial, sub‐epithelial changes throughout carcinogenesis. Study Design/Materials and Methods In the standard hamster cheek pouch model for oral carcinogenesis (n = 36), in vivo OCT was used to image epithelial and sub‐epithelial change. OCT‐ and histopathology‐based diagnoses on a scale of 0 (healthy) to 6 (squamous cell carcinoma, SCC) were performed at all stages throughout carcinogenesis by two blinded investigators. Results Epithelial, sub‐epithelial structures were clearly discernible using OCT. OCT diagnosis agreed with the histopathological gold standard in 80% of readings. Conclusion In vivo OCT demonstrates excellent potential as a diagnostic tool in the oral cavity. Lasers Surg. Med. 35:269–275, 2004. © 2004 Wiley‐Liss, Inc.